Padronização da densidade mineral óssea (DMO) do acessório do carpo em eqüinos atletas da raça Quarto de Milha - Vulcano, Luiz Carlos [UNESP]; Mendes, Rodrigo Guerrero [UNESP]; Godoy, Carmen Lice Buchmann de; Machado, Vania Maria de Vasconcelos [UNESP]; Bicudo, Alexandre Luiz da Costa [UNESP] (Universidade Federal de Santa Maria (UFSM), 2006)
Eqüinos da raça Quarto de Milha, 30 machos e 30 fêmeas com idade entre 42 e 48 meses, apresentando a epífise distal do rádio fechada, em plena atividade esportiva, foram analisados quanto à densidade mineral óssea (DMO) do acessório do carpo, tendo os valores expressos em milímetros de alumínio (mmAl). As radiografias da estrutura óssea, juntamente com uma escala de alumínio (penetrômetro) foram analisadas por meio de um programa computacional, especialmente desenvolvido para medida da densidade óptica em imagem radiográfica. O valor médio encontrado para as fêmeas foi de 4,49±0,69mmAl, com idade média de 43±2 meses e, para os machos, de 4,43 ± 0,81mmAl, com idade média de 45±2 meses, não havendo diferença significativa na DMO entre os sexos.

The bone mineral density (BMD) of the accessory carpal bone was measured (in aluminum millimeters - mmAl) in 30 female and 30 male Quarter Horse equines aging between 42 and 48 months that presented distal epiphysis of the radio closed, in full activity, using optical densitometry in radiographic images. Evaluation was made using a software specially developed for optical density measurement in X-ray films, containing the radiographic image of the accessory carpus bone, the region of soft parts adjacent to the accessory carpus and the degrees of an aluminum step wedge, used to measure BMD value (average of the interest region established on the accessory carpus bone corresponding to the value on the step wedge in millimeters/aluminum ( mmAl)). BMD values found for female were 4.49 ± 0.69mm Al with age of 43 ± 2 months e for male 4.43 ± 0.8mm Al, with average age 45 ± 2 months not show differences statistically significant in BMD values among sexes.
Padronization of bone mineral density (BMD) of the acessory carpus in Quarter Horse equines
Keywords: radiologia; eqüinos; densitometria óssea; radiology; equine; bone densitometry